Effects of a Large Dust Storm in the Near‐Surface Atmosphere as Measured by InSight in Elysium Planitia, Mars. Comparison With Contemporaneous Measurements by Mars Science Laboratory. Issue 9 (10th September 2020) - Viúdez‐Moreiras, D.; Newman, C. E.; Forget, F.; Lemmon, M.; Banfield, D.; Spiga, A.; Lepinette, A.; Rodriguez‐Manfredi, J. A.; Gómez‐Elvira, J.; Pla‐García, J.; Muller, N.; Grott, M.; et al.
Abstract: NASA's InSight landed in Elysium Planitia ( 4.5°N, 136°E) at Ls 296° (November 2018), right after the decay of the 2018 Global Dust Storm (GDS) and before the onset of the 2019 Large Dust Storm (LDS) at Ls 320° (January 2019). InSight's cameras observed a rise in the atmospheric opacities during the storm from 0.7 to 1.9, similarly to contemporaneous measurements by Curiosity in Gale crater. Pressure tides were strongly affected at the locations of InSight and Curiosity. In particular, the diurnal pressure mode experienced an abrupt increase during the onset of the LDS, similar to that measured by Curiosity, most likely due to longitudinally asymmetric dust loading. Later, the dust was redistributed around the planet and the semidiurnal mode evolved according to dust opacity in both missions. Before and after the onset of the storm, the observed wind patterns resulted from the interaction between regional and local slope flows induced by topography, which all produced a diurnal perturbation superimposed on a mean flow, dominated by the Hadley cell but with modifications due to channeling effects from the regional topography. However, the onset of the LDS modified this to a scenario consistent with enhanced tidal flows. The local air temperatures are strongly perturbed by the lander's thermal effects, and their retrieval significantly depends on wind patterns, which changed during the course of the dust storm. Observations suggest a decrease in convective vortices during the dust storm; however, vortex activity remained strong during the storm's onset due to the increase in wind speeds. Plain Language Summary: NASA's InSight landed in Elysium Planitia, Mars, at November 2018, right after the decay of the 2018 Global Dust Storm and before the onset of the 2019 Large Dust Storm (LDS) (January 2019). InSight's cameras observed a rise in the atmospheric opacities during the storm from 0.7 to 1.9, similar to contemporaneous measurements by Curiosity in Gale crater. Pressure tides were strongly affected. In particular, the amplitude of the pressure harmonics with a period of 1 sol (diurnal pressure mode) experienced an abrupt increase during the onset of the LDS, similar to that measured by Curiosity, most likely as a result of different dust loading as a function of location. Later, the dust was redistributed around the planet and the semidiurnal pressure mode evolved according to dust opacity in both missions. The onset of the storm modified the wind patterns, probably due to enhanced tidal flows. The measured air temperatures were strongly perturbed by the lander's thermal effects. The daytime lander effects significantly depend on wind patterns. Observations suggest an impact on convective vortices, with an overall decrease during the LDS. However, the vortex activity remained strong during storm onset due to the increase in wind speeds. Key Points: InSight measured the atmospheric response to a large dust storm at Ls 320° in MY34 Diurnal pressure amplitudes abruptly increased and vortex pressure drop decreased after an initial increase during storm onset Storm onset strongly modified flows dominated by the Hadley circulation and local slopes to include the effect of enhanced tidal flows